Handbook of real-world applications in modeling and simulation - Sokolowski, John A., 1953-; Banks, Catherine M., 1960- (Wiley handbooks in operations research and management science., 2012)
This handbook provides a thorough explanation of modeling and simulation in the most useful, current, and predominant applied areas, such as transportation, homeland security, medicine, operational research, military science, and business modeling. The authors offer a concise look at the key concepts and techniques of modeling and simulation and then discuss how and why the presented domains have become leading applications. The book begins with an introduction of why modeling and simulation is a reliable analysis assessment tool for complex syste.